Peculiarities in the formation, structural-mechanical properties of a fibrin-blood clot and its importance for bone regeneration in fractures - Popsuishapka, Olexii; Litvishko, Valeriy; Ashukina, Nataliya; Danishchuk, Zinayda (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The authors examined venous blood of three volunteers and determined the time of the formation (45-60 minutes) of a fibrin-blood clot in closed space in vitro, as well as they studied the effects of mechanical factors (pressure and mixing) on the rate of this formation. Dependence of the structure and mechanical properties of the formed fibrin upon the above factors was revealed. Histomorphological peculiarities of fibrin-blood clots, obtained from perifragmental regions in 12 cases with closed fractures of their extremities from 2 hours to 12 days after the injury, were studied. It was found out that poorly differentiated cells and fibroblasts entered the formed fibrin mesh on its periphery 2-4 hours after the fracture, and ingrowth of blood capillaries began. Reorganization of the clot was observed after 6-12 days.